Overview of Instructional Technology Used in the Education of Occupational Therapy Students: A Survey Study - Bryan M. Gee; Lisa Salazar; Jessica Porter; Camiel Clark; Theodore W. Peterson (Scholarworks @ WMU, 2017)
The purpose of this study was to explore the type of instructional technology (IT) master's degree level occupational therapy educational programs routinely use as a part of their lecture- and laboratory-based instruction. Surveying the administrators of 121 graduate occupational therapy programs in the United States, we found that the majority of the respondents identified their program as using IT in some form for lecturebased courses, with less inclusion of IT for laboratory-based courses. Hybrid instruction, with the majority of the content being delivered face-to-face and the remainder via online, were the trends among the respondents. The findings also indicated that the respondents' programs avoid certain IT, including synchronous online chat rooms or instant messaging, digital image collections, blogs or online journaling, Wikis, and audio/video podcasting. Few of the respondents said their programs had made a significant leap into implementing a larger online presence with instructional technology